Exploring the barriers of utilizing theoretical knowledge in clinical settings: A qualitative study - Mina Hashemiparast; Reza Negarandeh; Dimitrios Theofanidis (Elsevier, 2019)
Objectives: Although effective performance in clinical settings requires the integration between theory and practice, there is a gap between theoretical knowledge as taught in the classroom and what the students experience in clinical settings. This study aimed to elicit and explore the barriers of utilizing theoretical knowledge in clinical settings. Methods: A qualitative study was adopted with a conventional content analysis approach. Fifteen nursing and paramedic's students, faculty members and experienced nursing staff participated in the study. Data were collected by semi-structured individual interviews until data saturation and concurrently analyzed via MAXQDA 10. Results: Five main categories emerged as barriers of utilizing theoretical knowledge in the clinical settings i.e. non-standard practices in clinical settings; lack of trust in clinical competence; lack of perceived professional support; insufficiencies in teaching and learning process; and differences between doing things in simulated and real clinical situations. Conclusion: Transferring theory into practice in a structured manner requires professional support in the workplace, trust and the opportunity for direct experience, using valid and up-to-date knowledge by clinical staff and bridging the simulated situations with real life scenarios. Keywords: Clinical competence, Medical education, Knowledge, Practice, Qualitative research, Transfer